RACIAL DISCRIMINATION REFLECTED IN SERIES DRAMA TENNOUNORYOURIBAN (THE EMPEROR’S COOK) - Guruh Bimantara (Journal of Islamic World and Politics, 2020)
This paper discussed the discrimination that occurs in the life of Asian immigrants. Yellow Peril phenomenon occurs in 1882 in Europe and America which resulted in racial discrimination toward immigrants from China and Japan. In this study, the author uses data sources from a series drama entitled Tenno No Ryouriban (2015). This series drama showed the life of two immigrants from Japan named Tokuzo Akiyama and Shintaro Matsui who migrated to France. In their daily life, Tokuzo and Shintaro would frequently receive discrimination from white people. This study uses literal sociology. To obtain descriptions regarding discrimination, the author would analyze data in the form of scenes and dialogue excerpts are taken from the series drama Tenno No Ryouriban. Furthermore, there was also support theory Mise-En-Scene to help to explain the reason why a scene was shown in a particular manner by the film director. Result of this study showed that there were several scenes and dialogues excerpt which describe discrimination in various forms, such as Explicit Discrimination and Implicit Discrimination, and Institutional Discrimination and Cultural Discrimination. The author found the cause of discrimination described in the series drama Tenno No Ryouriban, which related to race differences such as differences in skin color, the nation of origin, and body height.